Measuring thermal spread during bipolar cauterizing using an experimental pneumoperitoneum and thermal sensors - Siracusano, Salvatore; Marchioro, Giacomo; Scutelnic, Dumitru; Brunelli, Matteo; Talamini, Renato; Porcaro, Antonio Benito; Fiorini, Paolo; Muradore, Riccardo; Daffara, Claudia (Frontiers in Surgery, 2023)
Objective During nerve-sparing robot-assisted radical prostatectomy (RARP) bipolar electrocoagulation is often used but its use is controversial for the possible thermal damage of neurovascular bundles. Aim of the study was to evaluate the spatial-temporal thermal distribution in the tissue and the correlation with the electrosurgery-induced tissue damage in a controlled, CO2-rich environment modelling the laparoscopy conditions.. Methods We manufactured a sealed plexiglass chamber (SPC) equipped with sensors to reproduce experimentally the environmental conditions of pneumoperitoneum during RARP. We evaluated in 64 pig musculofascial tissues (PMTs) of approximately 3 cm3 × 3 cm3 × 2 cm3 the spatial-temporal thermal distribution in the tissue and the correlation with the electrosurgery-induced tissue damage in a controlled CO2-rich environment modeling the laparoscopy conditions. Critical heat spread of bipolar cauterizing during surgical procedure was assessed by the employment of a compact thermal camera (C2) with a small core sensor (60 × 80 microbolometer array in the range 7–14 μm). Results Bipolar instruments used at 30 W showed a thermal spread area of 18 mm2 when applied for 2 s and 28 mm2 when applied for 4 s. At 60 W, bipolar instruments showed a mean thermal spread and 19 mm2 when applied for 2 s; and 21 mm2 when applied for 4 s. Finally, histopathological analysis showed that thermal damage is distributed predominantly on the surface rather than in depth. Conclusions The application of these results is very interesting for the definition of an accurate use of bipolar cautery during nerve-sparing RARP. It demonstrates the feasibility of using miniaturized thermal sensors, thus addressing the potential for next developments regarding the design of thermal endoscopic devices for robotic use.